Study of Efficacy and Acceptability of Levonorgestrel-Releasing Intrauterine Device in Heavy Menstrual Bleeding Patients - Robina Kousar; Fatima Sharif Khan; Tehreem Yazdani; Rehana Kousar; Fatima Mehmood; Mehwish Munir (Life and Science, 2024)
Objective: To determine the efficacy and acceptability of levonorgestrel-releasing intrauterine device (LNGIUD) in females with heavy menstrual bleeding (HMB). Study Design: A Quasi-experimental study design. Place and Duration of Study: The study was conducted at the Obstetrics and Gynecology Department of Pak Emirates Military Hospital (PEMH) Rawalpindi, Pakistan for a duration of 6 months from November 2022 to April 2023. Methods: A total of 96 patients accomplishing the selection criteria were enrolled after taking written informed consent after the screening, LNG-IUD was inserted in all participants and patients were followed up till the 6th menstrual cycle and outcomes (like having less bleeding or amenorrhea, improvement in hemoglobin, improvement in doing daily tasks, etc.) were assessed. Results: The mean age of the females was 38.08±5.83 years. Efficacy of treatment was seen in 64 (66.7%) females, and acceptability was seen in 61 (63.5%) females. In terms of side effects, spotting occurred in 17 (17.7%) patients, amenorrhea in 3 (3.1%) patients, oligomenorrhea in 4 (4.2%) patients, weight gain in 6 (6.3%) patients, breast heaviness in 3 (3.1%) patients, 3(3.1%) females had mood fluctuations and 2 (2.1%) had depression. Conclusion: For treating females with HMB, LNG-IUD was efficacious in 66.7% of females and acceptable in 63.5% of females.